APPLICATION OF LOCAL MESHLESS METHOD FOR THE SOLUTION OF TWO TERM TIME FRACTIONAL-ORDER MULTI-DIMENSIONAL PDE ARISING IN HEAT AND MASS TRANSFER - Ahmad, Imtiaz; Ahmad, Hijaz; İnç, Mustafa; Yao, Shao-Wen; Almohsen, Bandar (Vinca Inst Nuclear Sci, 2020)
In this article, we presented an efficient local meshless method for the numerical treatment of two term time fractional-order multi-dimensional diffusion PDE. The demand of meshless techniques increment because of its meshless nature and simplicity of usage in higher dimensions. This technique approximates the solution on set of uniform and scattered nodes. The space derivatives of the models are discretized by the proposed meshless procedure though the time fractional part is discretized by Liouville-Caputo fractional derivative. The numerical results are obtained for 1-, 2- and 3-D cases on rectangular and non-rectangular computational domains which verify the validity, efficiency and accuracy of the method.
Keywords: two term diffusion equation; Liouville-Caputo derivative; Meshless method; radial basis function